A universal nanoreactor strategy for scalable supported ultrafine bimetallic nanoparticles synthesis. (November 2020) - Tian, Zhengbin; Dong, Chao; Yu, Qun; Ye, Run-Ping; Duyar, Melis S.; Liu, Jian; Jiang, Heqing; Wang, Guang-Hui
Graphical abstract: Abstract: Supported bimetallic catalysts have become an important class of catalysts in heterogeneous catalysis. Although well-defined bimetallic nanoparticles (BNPs) can be synthesized by seeded-growth in liquid phase, uniform deposition of these BNPs onto porous supports is very challenging. Here, we develop a universal nanoreactor strategy to directly fabricate the PdAu BNPs in the solid support of coral-like nitrogen-doped mesoporous polymer (NMP) with uniform dispersion in a large scale. This strategy is based on coordination chemistry to introduce the high-quality seeds of Pd nanoclusters and the Au ions into the NMP, and thus to be used as a nanoreactor for seeded growth of PdAu BNPs in solid state during thermal reduction. Many other supported Pd-based BNPs (diameters ranging from 2 to 3 nm) have also been successfully synthesized by adoption of this strategy, including PdRu, PdCo, PdNi, PdZn, PdAg and PdCu BNPs. As an example, the as-synthesized Pd1 Au1/4 sample shows enhanced catalytic performance in formic acid (FA) dehydrogenation compared with the monometallic analogues, indicating the synergistic effect between Pd and Au. In addition, the Pd1 Au1/4 product is molded into monolith without any binders due to its coral-like structure. The Pd1 Au1/4 monolith shows considerable activity in FA dehydrogenation with a turnover frequency (TOF) value of 3684 h −1 at 333 K, which is recycled five times without changes in activity. We believe that the nanoreactor strategy provides an effective route to synthesize various supported bimetallic catalysts that have potential for applications in green and sustainable catalytic processes.